Water Vapor Sorption Behavior of Arabinoxylan from Corn Pericarp - Tomoki Yoshida; Wahyu Dwianto; Yoichi Honda; Hiroshi Uyama; Jun-ichi Azuma (Wood Research Journal, 2013)
The influence of the degree of arabinose substitution in arabinoxylan on its water vapor sorption behavior was investigated by comparing the application of the independent dual sorption model and the Hailwood-Horrobin (H-H) model on corn pericarp arabinoxylans with arabinose/xylose ratios of 0.35, 0.26 and 0.12. Characterization of their sigmoid shaped adsorption isotherms grouped in IUPAC Type II indicates the usefulness of the former model to demonstrate the importance of arabinose substituents in increasing the affinity of corn pericarp arabinoxylan for water molecules. The present results open the future applicability of the independent dual sorption model for characterization of the hydration behavior of other branched polymers.